Independent Man The Life of Senator James Couzens - Barnard, Harry (Wayne State University Press, 2002)
First published in 1958 by Charles Scribner's Sons, Independent Man is the only book-length biography of one of Michigan's most remarkable men. His many careers embraced both the business and political spheres. Couzens was a prominent business man who helped shape Ford Motor Company but he left the company when he and Henry Ford clashed over politics. Upon leaving Ford, Couzens began his career in politics. He first served as Detroit's police commissioner. He went on to a controversial term as mayor of Detroit and then represented Michigan in the U. S. Senate. This book reveals the life of a truly unique and inspirational man.